2014
DOI: 10.1089/ham.2014.1088
|View full text |Cite
|
Sign up to set email alerts
|

High Altitude Pilgrimage Medicine

Abstract: Religious pilgrims have been going to high altitude pilgrimages long before trekkers and climbers sojourned in high altitude regions, but the medical literature about high altitude pilgrimage is sparse. Gosainkunda Lake (4300 m) near Kathmandu, Nepal, and Shri Amarnath Yatra (3800 m) in Sri Nagar, Kashmir, India, are the two sites in the Himalayas from where the majority of published reports of high altitude pilgrimage have originated. Almost all travels to high altitude pilgrimages are characterized by very r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 41 publications
0
15
0
1
Order By: Relevance
“…There are several high-altitude pilgrimage sites in South Asia which are annually visited by millions of pilgrims. The important ones are Kailash Manasarovar in Tibet (>5000 m, estimated pilgrims annually 40 000); Gosainkund (4380 m, estimated pilgrims annually 10 000–20 000), Muktinath (3700 m, estimated pilgrims annually 30 000), Damodhar Kunda (4800 m, no data available on annual estimated pilgrims), Dudh Kunda (4500 m, no data available on annual estimated pilgrims) and Tilicho Lake (4900 m, no data available on annual estimated pilgrims) in Nepal; and Sri Amarnath (3800 m, estimated pilgrims annually 400 000–600 000), Kedarnath (3500 m, estimated pilgrims annually 600 000) and Badrinath (3100 m, estimated pilgrims annually 100 000) in India 6…”
Section: Global Health Problem Analysismentioning
confidence: 99%
“…There are several high-altitude pilgrimage sites in South Asia which are annually visited by millions of pilgrims. The important ones are Kailash Manasarovar in Tibet (>5000 m, estimated pilgrims annually 40 000); Gosainkund (4380 m, estimated pilgrims annually 10 000–20 000), Muktinath (3700 m, estimated pilgrims annually 30 000), Damodhar Kunda (4800 m, no data available on annual estimated pilgrims), Dudh Kunda (4500 m, no data available on annual estimated pilgrims) and Tilicho Lake (4900 m, no data available on annual estimated pilgrims) in Nepal; and Sri Amarnath (3800 m, estimated pilgrims annually 400 000–600 000), Kedarnath (3500 m, estimated pilgrims annually 600 000) and Badrinath (3100 m, estimated pilgrims annually 100 000) in India 6…”
Section: Global Health Problem Analysismentioning
confidence: 99%
“…In research on mountain sickness identi cation, researchers use the Lake Louise score (LLS) [20][21][22][23]and visual analogue score (VAS) [24][25][26] to identify acute mountain sickness. The internal factors that affect acute altitude sickness include obesity [27], age [28][29][30], sleep [31], hydration and in ammatory response [32], and psychological factors [33]. The external factors include low temperature, dryness, hypoxia [33].…”
Section: Introductionmentioning
confidence: 99%
“…Even though the demographics are not available, the authors have arbitrarily observed that most of them are from Hindi-speaking regions of India. Every year thousands of worshippers from all over India travel to Shri Amarnath Yatra (12,700 ft); Hemkund Sahib (14,000 ft); Manasarovar, (14,700m) 10 . Pilgrims traveling to high altitude are a vulnerable group 11 .…”
Section: Introductionmentioning
confidence: 99%